Preparation method of pH-sensitive composite flame-retardant hydrogel

CN122917344APending Publication Date: 2026-10-16CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510404698.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]本发明的目的是旨在提供一种pH敏感的水凝胶及其制备方法,针对水、惰性气体和哈龙等传统灭火剂在扑灭锂电池明火后可能迅速复燃,进而导致火灾再次失控的问题

Benefits of technology

[0029] This invention modifies nano-silica with an aminosilane coupling agent and reacts it with ammonium polyphosphate to form a silica coating layer. This effectively controls the release rate of ammonium polyphosphate, preventing excessively rapid release, while retaining the properties of ammonium polyphosphate decomposition to form a protective layer, reduce temperature, and slow flame propagation. The high thermal stability of nano-silica significantly improves the performance of the hydrogel in high-temperature environments. Synergistically, it works with ammonia gas generated by the thermal decomposition of APP to greatly enhance the thermal stability of the hydrogel, enabling it to better adapt to high-temperature conditions in fire situations. It can rapidly gel in the event of battery thermal runaway, forming a three-dimensional network structure to cover the fire source and isolate oxygen, providing continuous protection. Uncontacted colloids can maintain fluidity and continue to penetrate into other high-temperature areas, effectively isolating oxygen, absorbing and locking in acidic gases, and reducing the risk of reignition. Furthermore, all raw materials used in this invention are non-toxic and pollution-free, environmentally friendly, and leave no harmful residues after use. The raw materials are also inexpensive, economical, and have broad application prospects and market value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917344A_ABST
    Figure CN122917344A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium ion battery safety, and discloses a preparation method of a pH-sensitive composite flame-retardant hydrogel, which comprises the following steps: dispersing 10-15 g of nanometer silicon dioxide in 20-30 mL of concentrated nitric acid with a concentration of 40-45%, ultrasonic dispersion is carried out under the condition of an ultrasonic power of 250-300 W and a frequency of 40-50 kHz for 25-35 minutes, then centrifugal separation is carried out at 3500-4000 rpm for 10-15 minutes, and the solid is dried in a nitrogen atmosphere at 60-80 DEG C for 6-8 hours to obtain activated silicon dioxide; 20-25 g of ammonium polyphosphate is ground to 50-100 meshes and then dispersed in 400-500 mL of anhydrous ethanol, dispersion is carried out under the condition of an ultrasonic power of 250-300 W and a frequency of 40-50 kHz for 25-35 minutes to form a uniform APP suspension. The preparation method of the pH-sensitive composite flame-retardant hydrogel aims at the problem that traditional extinguishing agents such as water, inert gas and halon may quickly reignite after extinguishing the open fire of a lithium battery, and further cause the fire to be out of control again.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery safety technology, specifically to a method for preparing a pH-sensitive composite flame-retardant hydrogel. Background Technology

[0002] With the widespread application of lithium batteries in new energy vehicles, portable electronic devices, and energy storage, their fire safety hazards are becoming increasingly prominent. Thermal runaway has become a major cause of frequent fires. During thermal runaway, the internal temperature of the battery rises sharply, triggering the decomposition of the electrolyte and releasing a large amount of flammable gas. When these gases mix with oxygen, they are highly likely to ignite or even explode at high temperatures, creating a vicious cycle that greatly exacerbates the fire risk. To address this challenge, existing technologies mainly focus on optimizing the battery thermal management system and innovating fire extinguishing technologies. On the one hand, by improving battery design, such as using more stable electrode materials, optimizing electrolyte formulations, and enhancing battery heat dissipation structures, the intrinsic safety of the battery is improved. On the other hand, highly efficient fire extinguishing agents and fire extinguishing systems, such as gaseous fire extinguishing agents and fine water mist fire extinguishing systems, are being developed to quickly suppress the fire and prevent the spread of thermal runaway.

[0003] Traditional fire extinguishing agents, such as foam and halon, have certain shortcomings in dealing with lithium battery fires. Foam extinguishing agents mainly extinguish fires by covering the fire source and isolating oxygen, but their extinguishing effect is often limited in the face of the continuous thermal runaway reaction and flammable gas release inside lithium batteries, making it difficult to completely extinguish the fire and prevent reignition. Halon extinguishing agents, although once widely used for their high fire extinguishing performance, are strictly restricted by international agreements because they contain substances that damage the ozone layer, and their residues after extinguishing fires may cause long-term environmental pollution. Furthermore, these traditional fire extinguishing agents have not fundamentally solved the chain reaction caused by thermal runaway of lithium batteries and cannot effectively interrupt the exothermic process inside the battery. Summary of the Invention

[0004] The purpose of this invention is to provide a pH-sensitive hydrogel and its preparation method, addressing the problem that traditional fire extinguishing agents such as water, inert gases, and halons may rapidly reignite after extinguishing open flames in lithium batteries, leading to a renewed loss of control of the fire.

[0005] The technical solution of the present invention to solve the above-mentioned technical problems is as follows:

[0006] A method for preparing a pH-sensitive composite flame-retardant hydrogel includes the following steps:

[0007] Preparation of S10 nano-silica coated ammonium polyphosphate:

[0008] S101. Disperse 10-15g of nano-silica in 20-30mL of concentrated nitric acid with a concentration of 40-45%, and sonicate for 25-35 minutes under ultrasonic power of 250-300W and frequency of 40-50kHz. Then centrifuge at 3500-4000rpm for 10-15 minutes. After centrifugation, dry the solid at 60-80℃ for 6-8 hours in a nitrogen atmosphere to obtain activated silica.

[0009] S102. Grind 20-25g of ammonium polyphosphate to 50-100 mesh and disperse it in 400-500mL of anhydrous ethanol. Disperse it for 25-35 minutes under ultrasonic power of 250-300W and frequency of 40-50kHz to form a uniform APP suspension.

[0010] S103. Dissolve 3-5g of 3-aminopropyltriethoxysilane in 300-400mL of anhydrous ethanol, add 10-15g of activated silica, and react at 50-60℃ for 6-12 hours. After the reaction is complete, wash with deionized water and anhydrous ethanol 3-5 times each. After washing, dry at 60-80℃ under a nitrogen atmosphere to constant weight to obtain aminated silica.

[0011] S104. Mix the APP suspension from S102 with 50-60 mL of a mixed solution, which consists of 10-15% acetic acid and 50-60% hydrogen peroxide in a volume ratio of 5:1. Add 5-6 g of aminated silica solid and stir at 300-500 rpm for 1-2 hours at 25-30°C. Then centrifuge at 3500-4000 rpm for 10-15 minutes and wash 3-5 times. The resulting solid is dried in two stages: the first stage is pre-drying at 40-50°C for 6-8 hours, and the second stage is final drying at 70-80°C for 12-16 hours under nitrogen protection throughout. After drying, grind to 50-100 mesh to obtain nano-silica-coated ammonium polyphosphate powder.

[0012] S20, colloidal mixture:

[0013] S201. Dissolve 12-15g of low-methoxyl pectin in 1-1.5L of deionized water and stir magnetically at 500-700rpm until completely dissolved.

[0014] S202, add 20-40 g / L calcium-based bentonite and 20-30 g / L sodium-based bentonite in sequence, wherein the mass ratio of calcium-based bentonite to sodium-based bentonite is 1:1.5-2, and stir with an electric stirrer at 800-1200 rpm until there are no visible particles in the colloid.

[0015] S203, add 8-12 g / L of nano-silica coated ammonium polyphosphate powder, and stir at 1000-1200 rpm for 30-40 minutes until the colloidal viscosity reaches 2000-3000 mPa·s;

[0016] S30, Gel Molding:

[0017] S301. Place the S203 colloid in an ultrasonic disperser and ultrasonically disperse it for 30-40 minutes at 250-300W and 40-50kHz. Then, introduce nitrogen gas and let it stand for 1.5-2.5 hours to eliminate air bubbles.

[0018] S302. Inject the defoamed pregel into a mold and freeze it at -15℃ to -25℃ for 5-8 hours. Then thaw it in a constant temperature environment of 25-30℃ for 0.5-1.5 hours to obtain a pH-responsive flame-retardant hydrogel.

[0019] Based on the above technical solution, the present invention can be further improved as follows.

[0020] Furthermore, the concentration of concentrated nitric acid in S101 is 65-68%, and the solid-liquid ratio of nano-silica to nitric acid is 1:2-3 g / mL.

[0021] Furthermore, in S103, the mass ratio of 3-aminopropyltriethoxysilane to activated silica is 1:3-5, and 1-2% by volume of hydrochloric acid is added as a catalyst during the reaction.

[0022] Furthermore, in S104, the volume ratio of the acetic acid to hydrogen peroxide mixture is 5:1, and the pH value of the mixture is controlled within the range of 2.5-3.5.

[0023] Furthermore, the order in which calcium-based bentonite and sodium-based bentonite are added in S202 can be interchanged. After the interchange, an additional 10-15 minutes of stirring is required to ensure uniform dispersion.

[0024] Furthermore, the nano-silica-coated ammonium polyphosphate powder in S203 has a particle size of 50-100 mesh and a surface amino functional group content of 0.8-1.2 mmol / g.

[0025] Furthermore, in S301, after ultrasonic dispersion, nitrogen gas needs to be introduced at a flow rate of 10-20 L / min, and the settling time must be strictly controlled within 2 ± 0.2 hours.

[0026] Furthermore, in S302, the cooling rate during the freezing stage is 1-2℃ / min, and the heating rate during the thawing stage is 0.5-1℃ / min.

[0027] Furthermore, the hydrogel has a pH response range of 4.0-6.5, and the hydrogel needs to undergo a secondary drying process after preparation: the gel is placed in a vacuum drying oven and dried for 2-4 hours at 50-60℃ and a vacuum degree ≤0.1MPa to remove residual moisture and improve mechanical strength.

[0028] Compared with the prior art, the technical solution of this application has the following beneficial technical effects:

[0029] This invention modifies nano-silica with an aminosilane coupling agent and reacts it with ammonium polyphosphate to form a silica coating layer. This effectively controls the release rate of ammonium polyphosphate, preventing excessively rapid release, while retaining the properties of ammonium polyphosphate decomposition to form a protective layer, reduce temperature, and slow flame propagation. The high thermal stability of nano-silica significantly improves the performance of the hydrogel in high-temperature environments. Synergistically, it works with ammonia gas generated by the thermal decomposition of APP to greatly enhance the thermal stability of the hydrogel, enabling it to better adapt to high-temperature conditions in fire situations. It can rapidly gel in the event of battery thermal runaway, forming a three-dimensional network structure to cover the fire source and isolate oxygen, providing continuous protection. Uncontacted colloids can maintain fluidity and continue to penetrate into other high-temperature areas, effectively isolating oxygen, absorbing and locking in acidic gases, and reducing the risk of reignition. Furthermore, all raw materials used in this invention are non-toxic and pollution-free, environmentally friendly, and leave no harmful residues after use. The raw materials are also inexpensive, economical, and have broad application prospects and market value. Attached Figure Description

[0030] Figure 1 This is a flowchart illustrating the preparation method of a pH-sensitive composite flame-retardant hydrogel according to the present invention. Detailed Implementation

[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] The present invention discloses a method for preparing a pH-sensitive composite flame-retardant hydrogel, comprising the following steps:

[0033] Preparation of S10, nano-silica coated ammonium polyphosphate (APP@nano-SiO2):

[0034] S101. Disperse 10-15g of nano-SiO2 in 20-30mL of concentrated nitric acid with a concentration of 40-45%. Sonicate the dispersion for 25-35 minutes at an ultrasonic power of 250-300W and a frequency of 40-50kHz. Then centrifuge at 3500-4000rpm for 10-15 minutes. After centrifugation, dry the solid at 60-80℃ for 6-8 hours in a nitrogen atmosphere to obtain activated silica. The concentration of concentrated nitric acid in S101 is 65-68%, and the solid-liquid ratio of nano-silica to nitric acid is 1:2-3g / mL.

[0035] S102. Grind 20-25g of ammonium polyphosphate (APP) to 50-100 mesh and disperse it in 400-500mL of anhydrous ethanol. Disperse it for 25-35 minutes under ultrasonic power of 250-300W and frequency of 40-50kHz to form a uniform APP suspension.

[0036] S103: Dissolve 3-5g of 3-aminopropyltriethoxysilane (APTES) in 300-400mL of anhydrous ethanol, add 10-15g of activated silica, and react at 50-60℃ for 6-12 hours. After the reaction, wash with deionized water and anhydrous ethanol 3-5 times each. After washing, dry at 60-80℃ under a nitrogen atmosphere to constant weight to obtain aminated silica. The mass ratio of 3-aminopropyltriethoxysilane to activated silica in S103 is 1:3-5, and 1-2% by volume of hydrochloric acid is added as a catalyst during the reaction.

[0037] S104. Mix the APP suspension from S102 with 50-60 mL of a mixed solution consisting of 10-15% acetic acid and 50-60% hydrogen peroxide in a volume ratio of 5:1. Add 5-6 g of aminated silica solid and stir at 300-500 rpm for 1-2 hours at 25-30℃. Then centrifuge at 3500-4000 rpm for 10-15 minutes and wash 3-5 times. The resulting solid is dried in two stages: the first stage is pre-drying at 40-50℃ for 6-8 hours, and the second stage is final drying at 70-80℃ for 12-16 hours under nitrogen protection throughout. After drying, grind to 50-100 mesh to obtain nano-silica-coated ammonium polyphosphate powder. The volume ratio of acetic acid to hydrogen peroxide in the mixed solution in S104 is 5:1, and the pH value of the mixed solution is controlled within the range of 2.5-3.5.

[0038] S20, colloidal mixture:

[0039] S201. Dissolve 12-15g of low methoxyl pectin (LMP, purity ≥95%) in 1-1.5L of deionized water and stir magnetically at 500-700rpm until completely dissolved.

[0040] S202, add 20-40 g / L calcium-based bentonite (Ca-Bt) and 20-30 g / L sodium-based bentonite (Na-Bt) in sequence, wherein the mass ratio of calcium-based bentonite to sodium-based bentonite is 1:1.5-2. Stir with an electric stirrer at 800-1200 rpm until there are no visible particles in the colloid. The order of adding calcium-based bentonite and sodium-based bentonite in S202 can be interchanged. After interchangement, it is necessary to stir for an additional 10-15 minutes to ensure uniform dispersion.

[0041] Add 8-12 g / L of nano-silica-coated ammonium polyphosphate powder to S203, and stir at 1000-1200 rpm for 30-40 minutes until the colloidal viscosity reaches 2000-3000 mPa·s. The particle size of the nano-silica-coated ammonium polyphosphate powder in S203 is 50-100 mesh, and the content of its surface amino functional groups is 0.8-1.2 mmol / g.

[0042] S30, Gel Molding:

[0043] S301. Place the colloid of S203 in an ultrasonic disperser and ultrasonically disperse it for 30-40 minutes at 250-300W and 40-50kHz. Then, introduce nitrogen gas and let it stand for 1.5-2.5 hours to eliminate air bubbles. After ultrasonic dispersion in S301, the flow rate of nitrogen gas should be 10-20L / min, and the standing time should be strictly controlled within 2±0.2 hours.

[0044] S302. The defoamed pregel is injected into a mold and frozen at -15℃ to -25℃ for 5-8 hours, followed by thawing at a constant temperature of 25-30℃ for 0.5-1.5 hours to obtain a pH-responsive flame-retardant hydrogel. The cooling rate during the freezing stage in S302 is 1-2℃ / min, and the heating rate during the thawing stage is 0.5-1℃ / min. The pH response range of the hydrogel is 4.0-6.5. After preparation, the hydrogel needs to undergo a secondary drying treatment: the gel is placed in a vacuum drying oven and dried at 50-60℃ and a vacuum degree ≤0.1MPa for 2-4 hours to remove residual moisture and improve mechanical strength.

[0045] Example 1: Preparation method of ammonium polyphosphate (APP@nano-SiO2) coated with nano-silica:

[0046] Take 10g of nano-SiO2 and add it to deionized water. Use a magnetic stirrer to maintain a stirring speed of 500-700rpm and wash repeatedly with plasma water until the washing solution is colorless and transparent. Then, slowly dissolve the washed SiO2 in 20mL of concentrated nitric acid and ultrasonically disperse it for 25-30 minutes under ultrasonic power of 250W and frequency of 40kHz to form a suspension. Centrifuge the suspension and put the centrifuged activated silica solid into an oven to dry in a N2 atmosphere at a controlled temperature of 60-80℃.

[0047] Take 20g of solid ammonium polyphosphate into an agate mortar and grind it to 50-100 mesh. Then slowly dissolve the ground ammonium polyphosphate in 400mL of anhydrous ethanol and ultrasonically disperse it for 25-30 minutes under ultrasonic power of 250W and frequency of 40kHz to form a suspension.

[0048] Dissolve 3g of 3-aminopropyltriethoxysilane (APTES) in 300mL of anhydrous ethanol. Use a magnetic stirrer to maintain a stirring speed of 300-500rpm to obtain an APTES solution (1.5%). Add 10g of dried activated silica to the APTES solution and react at 50-60℃ for 6-12 hours. After the reaction is complete, wash the solid with water and alcohol according to the silica washing procedure. Place the washed solid in an oven and dry it in a N2 atmosphere at a controlled temperature of 60-80℃ to obtain aminated silica solid.

[0049] Slowly add the prepared APP suspension to 50 mL of a solution prepared by mixing 10% acetic acid and 50% hydrogen peroxide (50%) at a volume ratio of 5:1. Then add 5 g of aminated silica solid and stir at room temperature for 1-2 hours, maintaining a stirring speed of 300-500 rpm. Control the solution temperature at 25-30℃ during the process to avoid affecting the dispersibility of APP particles. Transfer the mixture to centrifuge tubes and centrifuge multiple times (3500 rpm, 10-15 minutes each time). After each centrifugation, remove the supernatant. The mixture was repeatedly washed with deionized water for 10-15 minutes each time to obtain a suspension of ammonium polyphosphate coated with amino-modified nano-silica. The centrifugation and washing process was repeated, and the centrifuged particle complex was transferred to a vacuum drying oven. Under a nitrogen protective atmosphere, it was pre-dried at a low temperature (40-50℃, 6-8 hours) and then dried at a higher temperature (70-80℃, 12-16 hours). The mixture was then ground into powder and finally dried in a vacuum oven at 80℃ to constant weight for 6 hours to obtain a ready-to-use product.

[0050] Preparation of pH-sensitive flame-retardant hydrogel:

[0051] At room temperature, LMP was dissolved in 1L of deionized water and stirred at 500 rpm with a magnetic stirrer until completely dissolved. Ca-Bt was added to the colloid and stirred with an electric stirrer until no obvious Ca-Bt particles were found in the colloid. Na-Bt was added to the colloid and stirred with an electric stirrer until no obvious Na-Bt particles were found in the colloid. 10g of APP@nano-SiO2 was taken and stirred with an electric stirrer at 1000 rpm for 30 minutes until the viscosity of the solution increased. The pretreated colloid was placed in an ultrasonic disperser and ultrasonically dispersed for 30 minutes at a power of 250W and a frequency of 40kHz to allow LMP molecules to insert between the Bt layers. The mixture was allowed to stand for 2 hours under a N2 atmosphere to allow the bubbles to completely dissipate. Finally, the pregel was injected into a mold and frozen at -20℃ for 6 hours. After freezing, it was thawed at room temperature for 1 hour to obtain a pH-sensitive flame-retardant hydrogel.

[0052] The required formulation for the flame retardant is as follows: 10g of nano silica (SiO2), 3g of 3-aminopropyltriethoxysilane (APTES), 300mL of ethanol (95%), 25mL of acetic acid (10%), 5mL of concentrated nitric acid (40%), and 50% hydrogen peroxide.

[0053] The required formulation for colloid preparation is: 12 g / L low methoxy pectin (LMP), 20-40 g / L calcium-based bentonite (Ca-Bt), 20-30 g / L sodium-based bentonite (Na-Bt), and 10 g / L APP@nano-SiO2.

[0054] The initial decomposition temperature, water absorption rate, and viscosity of the hydrogel were analyzed.

[0055] First, the experiment was conducted using a thermogravimetric analysis (TGA) instrument. Approximately 10 mg of hydrogel sample was placed in the sample pan of the TGA instrument. The temperature range was set from 25 °C to 800 °C, the heating rate was 10 °C / min, the reaction gas flow rate was 40 mL / min, and the test was performed under a nitrogen atmosphere. During the heating process, the mass change of the sample was recorded, and the thermal decomposition curve was analyzed to determine the initial decomposition temperature (Td), i.e., the temperature at which the sample begins to experience significant weight loss.

[0056] Then, approximately 5 grams of the dried hydrogel sample was immersed in deionized water for 24 hours to ensure sufficient water absorption. Afterward, excess moisture was gently removed from the sample surface using filter paper, and the wet weight (W) was measured. w Then place it in a desiccator until constant weight, and record the dry weight (W). d The formula for calculating water absorption rate is: Water absorption rate (%) = (W) / (W) w -W d ) / W d ×100 Water absorption rate (%) = W d (Ww -W d )×100.

[0057] Finally, a rotational viscometer was used to prepare the hydrogel sample and place it in the measuring cup of the viscometer. Different shear rates were set (e.g., from 1 to 100 s). -1 The torque values ​​of the viscometer were recorded at various shear rates. Based on the torque values ​​and shear rates, the viscosity (Pa·s) of the sample was calculated. These experimental data allow for a comprehensive evaluation of the thermal stability, water absorption capacity, and rheological properties of the hydrogel, providing crucial information for its applications in fire extinguishing and materials science.

[0058]

[0059]

[0060] Table 1 Test parameters for different hydrogel properties

[0061] The experimental data above shows that the fire extinguishing effects of different types of hydrogels were evaluated in this experiment, including low-methoxyl pectin hydrogel, sodium alginate hydrogel, polyacrylamide (PAM) hydrogel, and polyurethane hydrogel. By comparing their initial decomposition temperature, water absorption rate, and viscosity, the following conclusions were drawn:

[0062] Below 128°C, mass loss is relatively slow, with approximately 22% loss, leaving 78% of the total mass. This is because unbound water in the extinguishing agent begins to vaporize after absorbing heat, while water tightly bound to the gel macromolecules remains in liquid form without significant change. As the temperature rises to between 128°C and 180°C, the mass loss of the hydrogel accelerates, primarily due to the breaking of polymer molecular chains and the decomposition of some substances, causing the previously tightly bound water to detach and rapidly vaporize. During this stage, the mass loss is significant, accounting for 85% of the total mass. The mass loss rate reaches its maximum at 180°C, approximately 1.3 g / °C. When the temperature continues to rise to 220°C, the remaining mass of the gel drops to 10% of the total mass; at this point, the water bound to the gel molecules has completely vaporized, and the water absorption rate remains at 450%. When the temperature is further increased to 220℃ to 700℃, the low-methoxylated pectin in the hydrogel begins to decompose, the glycosidic bonds between sugar units break, and galacturonic acid is generated. Galacturonic acid undergoes demethoxylation at high temperatures to generate methanol. After 700℃, the remaining mass accounts for about 5% of the total mass, and these residual substances contribute to the formation of the carbon layer.

[0063] Low-methoxyl pectin hydrogel exhibited the best fire extinguishing effect. Its initial decomposition temperature was 220℃, significantly higher than sodium alginate hydrogel and polyacrylamide hydrogel, indicating its stability at high temperatures. Furthermore, the low-methoxyl pectin hydrogel had a water absorption rate as high as 450%, making it excellent at absorbing moisture and forming an insulating layer, effectively slowing flame spread. Its viscosity of 1.2 Pa·s was moderate, allowing it to form a good covering effect during spraying, further enhancing its fire extinguishing performance.

[0064] Compared to other hydrogels, sodium alginate hydrogel has the highest water absorption rate (500%), but its initial decomposition temperature is low, potentially making it unstable at high temperatures. Polyacrylamide hydrogel has a relatively low water absorption rate (300%) and a viscosity of only 0.8 Pa·s, resulting in poor performance in fire extinguishing applications. While polyurethane hydrogel has relatively balanced properties, its overall performance is still inferior to low-methoxyl pectin hydrogel.

[0065] In conclusion, low-methoxyl pectin hydrogels, with their high thermal stability, excellent water absorption capacity, and moderate viscosity, demonstrate the best fire extinguishing effect and prove their application potential in fire response.

[0066] Experiment on the effects of different modification methods on the flame retardant properties and smoke suppression effect of ammonium polyphosphate

[0067] The table below shows the effects of different modification methods on the flame retardant properties and smoke suppression effect of ammonium polyphosphate. Thermogravimetric analysis (TGA) was performed on ammonium polyphosphate samples treated with different modification methods using a simultaneous thermal analyzer (TGA). The temperature range was set from 120 to 800℃, and the atmosphere was nitrogen (N2) to ensure that no oxygen participated in the thermal decomposition process. During heating, the mass change of the samples was monitored, and significant mass decrease peaks were recorded. Combined with the temperature change of 5% weight loss, the initial decomposition temperature of the samples was determined. This initial decomposition temperature reflects the thermal stability of the experimental samples and indicates the influence of the modification method on the pyrolysis performance. Simultaneously, the char residue at 800℃ was measured, i.e., the ratio of the remaining solid residue after heating to 800℃ to the initial mass. This indicator can be used to evaluate the charring ability and thermal decomposition resistance of the samples. A higher char residue generally indicates that the material can maintain good structural stability at high temperatures, which helps to improve flame retardant properties. Furthermore, in thermogravimetric analysis (TGA) experiments, the smoke release of the sample during heating was monitored in real time using a smoke measurement device (such as a thermogravimetric-smoke analysis system), and the total smoke generation (such as the release of gases like CO2 and CO) was recorded. This data reflects the smoke suppression effect of the sample; lower smoke release means that this modification method can effectively reduce the release of toxic gases in a fire and improve flame retardant performance. Experimental data show that the nano-SiO2 surface modification method can significantly increase the char residue rate of ammonium polyphosphate, and its initial decomposition temperature and smoke suppression effect are superior to other modification methods.

[0068]

[0069]

[0070] Table 2. Effects of different modification methods on the flame retardant properties and smoke suppression effect of ammonium polyphosphate (MPA).

[0071] Comparative test of fire extinguishing performance of different extinguishing agents

[0072] Experimental process

[0073] Experimental preparation stage:

[0074] 1) Battery preparation. Charge the 18650 lithium battery (2600mAh) to 100% charge using a dedicated lithium-ion battery charger.

[0075] State of Charge (SOC): Discharge the battery to 20% SOC according to a specific discharge curve, monitor the discharge process (approximately 3 hours), and allow it to stand for 12 hours after discharge to ensure the internal state of the battery is stable. Ensure that the experimental equipment is operated in a safe and well-ventilated environment.

[0076] 2) Equipment Debugging. Ensure the experimental equipment operates in a safe and well-ventilated environment. Place the instruments and equipment in the designated location and connect them to the computer. Start the relevant software on the computer and check the thermocouple connections for proper functioning and sensitivity. Simultaneously, verify the operational status of the mass sensor (to ensure accurate measurement of extinguishing agent dosage), gas sensor (to monitor harmful gas concentrations), infrared online thermometer (to monitor flame temperature in real time), high-definition camera (fixed in the experimental area to record the extinguishing process), and liquid nitrogen extinguishing system (check their operational status for rapid deployment).

[0077] The extinguishing agents to be selected include pH-sensitive hydrogel extinguishing agents, fluorinated aerosols, polymer hydrogels, and Lith-X (lithium salt extinguishing agents).

[0078] Experimental steps:

[0079] 1) Turn on the experimental instruments and equipment, turn on the computer, and activate the software associated with the instruments and equipment.

[0080] 2) Place the lithium-ion battery on a refractory stand, ignite the lithium-ion battery using an appropriate ignition device (such as a resistance wire), and record the ambient temperature at the time of ignition (approximately 25°C). In the liquid nitrogen injection experiment, turn off the power to the heating device at the moment of liquid nitrogen injection.

[0081] 3) After the experiment, save the data recorded by the instrument software to the corresponding location and turn off the instrument.

[0082] 4) Turn on the exhaust fan to exhaust smoke from the explosion-proof experimental chamber and restore room temperature, and let the heating plate stand still for 2 hours to cool down.

[0083]

[0084] Table 3 Comparison of fire extinguishing tests with different extinguishing agents

[0085] Based on the comparison of experimental results, the pH-sensitive hydrogel fire extinguishing agent performed exceptionally well in terms of fire extinguishing performance. This agent not only had the shortest release time, extinguishing the fire source rapidly in just 3 seconds, but also demonstrated superior cooling effect compared to other fire extinguishing agents, reducing the temperature by 67.21%. More importantly, no reignition was observed after extinguishing the fire, exhibiting extremely strong persistence and effectively ensuring the complete extinguishment of the fire source.

[0086] In contrast, while fluorinated aerosols, polymer hydrogels, and Lith-X (lithium salt fire extinguishing agents) also exhibited good cooling effects, all showed reignition, with reignition times of 90 seconds, 120 seconds, and 180 seconds, respectively, demonstrating their inadequacy in controlling the fire. Polymer hydrogels, in particular, despite a 4-second release time, showed significantly less cooling effect and fewer reignitions compared to pH-sensitive hydrogel fire extinguishing agents.

[0087] pH-sensitive hydrogel fire extinguishing agents are known for their rapid fire extinguishing response, significant cooling effect, and excellent ability to prevent reignition. The fire extinguishing test parameters of pH-sensitive hydrogel fire extinguishing agents were also tested, and the test results are shown in the table below.

[0088]

[0089] Table 4. Fire extinguishing test parameters for pH-sensitive hydrogel fire extinguishing agents

[0090] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0091] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a pH-sensitive composite flame-retardant hydrogel, characterized in that, Includes the following steps: Preparation of S10 nano-silica coated ammonium polyphosphate: S101. Disperse 10-15g of nano-silica in 20-30mL of concentrated nitric acid with a concentration of 40-45%, and sonicate for 25-35 minutes under ultrasonic power of 250-300W and frequency of 40-50kHz. Then centrifuge at 3500-4000rpm for 10-15 minutes. After centrifugation, dry the solid at 60-80℃ for 6-8 hours in a nitrogen atmosphere to obtain activated silica. S102. Grind 20-25g of ammonium polyphosphate to 50-100 mesh and disperse it in 400-500mL of anhydrous ethanol. Disperse it for 25-35 minutes under ultrasonic power of 250-300W and frequency of 40-50kHz to form a uniform APP suspension. S103. Dissolve 3-5g of 3-aminopropyltriethoxysilane in 300-400mL of anhydrous ethanol, add 10-15g of activated silica, and react at 50-60℃ for 6-12 hours. After the reaction is complete, wash with deionized water and anhydrous ethanol 3-5 times each. After washing, dry at 60-80℃ under a nitrogen atmosphere to constant weight to obtain aminated silica. S104. Mix the APP suspension from S102 with 50-60 mL of a mixed solution, which consists of 10-15% acetic acid and 50-60% hydrogen peroxide in a volume ratio of 5:

1. Add 5-6 g of aminated silica solid and stir at 300-500 rpm for 1-2 hours at 25-30°C. Then centrifuge at 3500-4000 rpm for 10-15 minutes and wash 3-5 times. The resulting solid is dried in two stages: the first stage is pre-drying at 40-50°C for 6-8 hours, and the second stage is final drying at 70-80°C for 12-16 hours under nitrogen protection throughout. After drying, grind to 50-100 mesh to obtain nano-silica-coated ammonium polyphosphate powder. S20, colloidal mixture: S201. Dissolve 12-15g of low-methoxyl pectin in 1-1.5L of deionized water and stir magnetically at 500-700rpm until completely dissolved. S202, add 20-40 g / L calcium-based bentonite and 20-30 g / L sodium-based bentonite in sequence, wherein the mass ratio of calcium-based bentonite to sodium-based bentonite is 1:1.5-2, and stir with an electric stirrer at 800-1200 rpm until there are no visible particles in the colloid. S203, add 8-12 g / L of nano-silica coated ammonium polyphosphate powder, and stir at 1000-1200 rpm for 30-40 minutes until the colloidal viscosity reaches 2000-3000 mPa·s; S30, Gel Molding: S301. Place the S203 colloid in an ultrasonic disperser and ultrasonically disperse it for 30-40 minutes at 250-300W and 40-50kHz. Then, introduce nitrogen gas and let it stand for 1.5-2.5 hours to eliminate air bubbles. S302. Inject the defoamed pregel into a mold and freeze it at -15℃ to -25℃ for 5-8 hours. Then thaw it in a constant temperature environment of 25-30℃ for 0.5-1.5 hours to obtain a pH-responsive flame-retardant hydrogel.

2. The method for preparing a pH-sensitive composite flame-retardant hydrogel according to claim 1, characterized in that, The concentration of concentrated nitric acid in S101 is 65-68%, and the solid-liquid ratio of nano-silica to nitric acid is 1:2-3 g / mL.

3. The method for preparing a pH-sensitive composite flame-retardant hydrogel according to claim 1, characterized in that, In the S103, the mass ratio of 3-aminopropyltriethoxysilane to activated silica is 1:3-5, and 1-2% by volume of hydrochloric acid is added as a catalyst during the reaction.

4. The method for preparing a pH-sensitive composite flame-retardant hydrogel according to claim 1, characterized in that, In S104, the volume ratio of the acetic acid to hydrogen peroxide mixture is 5:1, and the pH value of the mixture is controlled within the range of 2.5-3.

5.

5. The method for preparing a pH-sensitive composite flame-retardant hydrogel according to claim 1, characterized in that, The order in which calcium-based bentonite and sodium-based bentonite are added in S202 can be interchanged. After the interchange, an additional 10-15 minutes of stirring is required to ensure uniform dispersion.

6. The method for preparing a pH-sensitive composite flame-retardant hydrogel according to claim 1, characterized in that, The nano-silica-coated ammonium polyphosphate powder in S203 has a particle size of 50-100 mesh and a surface amino functional group content of 0.8-1.2 mmol / g.

7. The method for preparing a pH-sensitive composite flame-retardant hydrogel according to claim 1, characterized in that, After ultrasonic dispersion in S301, nitrogen gas needs to be introduced at a flow rate of 10-20 L / min, and the settling time must be strictly controlled within 2 ± 0.2 hours.

8. The method for preparing a pH-sensitive composite flame-retardant hydrogel according to claim 1, characterized in that, In S302, the cooling rate during the freezing stage is 1-2℃ / min, and the heating rate during the thawing stage is 0.5-1℃ / min.

9. The method for preparing a pH-sensitive composite flame-retardant hydrogel according to claim 1, characterized in that, The hydrogel has a pH response range of 4.0-6.

5. After preparation, the hydrogel needs to undergo a secondary drying process: the gel is placed in a vacuum drying oven and dried for 2-4 hours at 50-60℃ and a vacuum degree ≤0.1MPa to remove residual moisture and improve mechanical strength.